ENCHYTRAEIDS SUSTAINABILITY AND TOLERANCE AGAINST AGRO-CHEMICALS IN ZEA MAYS CROPLAND - S. L. DEZI; DEEPTI LAL; V. B. LAL (The Bioscan, 2012)
Enchytraeids, a true soil layer dwellers and indicator organisms, serves as an early warning system of the changes in composition and functioning of the soil system. A field monitoring of enchytraeid community against fertilizers and biocide application in conventionally tilled and no-tilled agro-ecosystems for maize was done for a period of 12 months. Impact of DAP 50 kg/ha, Potash 22kg/ha, Urea 10 kg/ha and BHC on Fridericia sp., Achaeta sp., Enchytraeus sp., Hemienchytraeus sp. and Marionina sp. of enchytraeids showed that overall population was reduced in treated plots at different dates of sampling by 45 to 55%. Among them Achaeta sp., Hemienchytraeus sp. and Marionina sp. were more sensitive. However Fridericia sp. and Enchytraeus sp., was dominant in both the agro-ecosystems addressing their sustainability. The time required for the restoration of their population ranged from several weeks to 8-10 months depending on the taxa.